School library management as a learning resource for achieving school quality report card standards at SMA Negeri 1 Silangkitang, South Labuhanbatu Regency - Khoyan Khoyan; Marlina Siregar; Aziddin Harahap; Junita Junita; Muhammad Ardansyah (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the planning, human resource procurement, development, and evaluation of school library management as a learning resource at SMA Negeri 1 Silangkitang, South Labuhanbatu Regency. A qualitative research approach was employed, involving the principal, head librarian, library staff, teachers, and students as research informants. Data were collected through interviews, observations, and document analysis related to library management. The findings reveal that school library management is systematically integrated into school programs to support literacy development and learning activities. Human resource management is implemented through the assignment of qualified librarians and staff, supported by continuous professional development through training and institutional collaboration. Library development focuses on expanding book collections, improving digital services, upgrading reading facilities, and strengthening literacy programs. Furthermore, library management is evaluated periodically using activity reports, library visitation records, and book circulation data to improve service quality. The study concludes that the school library functions as a strategic learning resource center that enhances learning quality, promotes a culture of literacy, and contributes to improving the overall quality of education at the school.